(untitled) (Asian Journal of Applied Sciences, 2017)
It has designed a portable device for halal verification of alcoholic beverages based on ethanol sensor technology using an electrochemical method. Two electrode electrochemical system has developed using nickel wire (Ni) as the working electrode (active) and platinum metal (Pt) as a counter electrode. The platinum electrode acts as an electrocatalyst that oxidizes ethanol by applying an electric voltage. The output current varies with the concentration of ethanol that decreased as the ethanol concentration increases. This output current is converted into an electric voltage, then was input into the microcontroller. The device output is displayed on the LCD in the percent volume (% volume) of ethanol concentration. From the measurement results note that the device designed can detect ethanol up to a concentration of 0.1% or lower. This device has also been tested and able to detect the presence of ethanol in some foods and beverages.